Trends in healthcare expenditure among people living with HIV/AIDS in the United States: evidence from 10 Years of nationally representative data - Tiarney D. Ritchwood; Kinfe G. Bishu; Leonard E. Egede (BMC, 2017)
Abstract Background While previous studies have examined HIV cost expenditures within the United States, the majority of these studies focused on data collected prior to or shortly after the advent and uptake of antiretroviral therapy, focused only on a short time frame, or did not provide cost comparisons between HIV/AIDS and other chronic conditions. It is critical that researchers provide accurate and updated information regarding the costs of HIV care to assist key stakeholders with economic planning, policy development, and resource allocation. Methods We used data from the Medical Expenditure Panel Survey-Household Component for the years 2002-2011, which represents a nationally representative U.S. civilian non-institutionalized population. Using generalized linear modeling, we estimated the adjusted direct medical expenditures by HIV/AIDS status after controlling for confounding factors. Results Data were from 342,732 people living with HIV/AIDS. After adjusting for socio-demographic factors, comorbidities and time trend covariates, the total direct expenditures for HIV/AIDS was $31,147 (95% CI $23,645-$38,648) or 800-900% higher when compared to those without HIV/AIDS (i.e., diabetes, stroke, and cardiovascular disease). Based on the adjusted mean, the aggregate cost of HIV/AIDS was approximately $10.7 billion higher than the costs for those without HIV/AIDS. Conclusions Our estimates of cost expenditures associated with HIV care over a 10-year period show a financial burden that exceeds previous estimates of direct medical costs. There is a strong need for investment in combination prevention and intervention programs, as they have the potential to reduce HIV transmission, and facilitate longer and healthier living thereby reducing the economic burden of HIV/AIDS.